2016
DOI: 10.1007/s10943-016-0332-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Religious Belief and Happiness: A Systematic Literature Review

Abstract: Happiness is a feeling that is desired by every human being. To achieve happiness, human try various routes like, to gain financial superiority, fame, entertainment, assets and so on. But on the contrary, religiosity is claimed to be a technique to attain purpose in life, mental health, physical well-being and internal peace, which ultimately leads to happiness in life. This study analyses the studies conducted in last two decades toward understanding the relationship between religiousness and happiness. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 62 publications
5
46
1
1
Order By: Relevance
“…Religion as a Coping Mechanism. Existing literature has found that religiosity is positively correlated with happiness (Rizvi and Hossain, 2017;Stavrova, Fetchenhauer, and Schlösser, 2013;Manglos, 2013, Sahraian et al, 2013May, 2018;Joshanloo and Weijers, 2016;Yeung 2018). This finding has been, to a large extent, consistent across countries and religious denominations.…”
Section: Religion and Happinessmentioning
confidence: 68%
See 3 more Smart Citations
“…Religion as a Coping Mechanism. Existing literature has found that religiosity is positively correlated with happiness (Rizvi and Hossain, 2017;Stavrova, Fetchenhauer, and Schlösser, 2013;Manglos, 2013, Sahraian et al, 2013May, 2018;Joshanloo and Weijers, 2016;Yeung 2018). This finding has been, to a large extent, consistent across countries and religious denominations.…”
Section: Religion and Happinessmentioning
confidence: 68%
“…There has also been great curiosity about the importance of income and religiosity (or spirituality) in our daily lives. The existing literature has focused largely on the relationship between income and happiness (Christoph 2010;Boes and Winkelmann 2010;Mentzakis and Moro 2009;Rukumnuaykit 2016) and the relationship between religiosity and happiness (Manglos 2013;Rizvi and Hossain 2017;Sahraian et al 2013;Stavrova, Fetchenhauer, and Schloesser 2013). Although there has been extensive research on the relationship between income and happiness and the relationship between religiosity and happiness, there are very few studies that explore the relationship between the three variables: income, religiosity, and happiness (Joshanloo and Weijers 2016).…”
Section: Religion As a Moderator Between Income And Happinessmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The Cramer's V statistic is appropriate for measuring correlations between two categorical variables and ranges between 0 and 1, with higher values indicating stronger correlations between the two variables. 10 This result obtained in a cross-country setting with nationally representative surveys from many developing countries, is not surprising, although it contrasts the findings of positive association between happiness and religiosity in country-specific studies using, in many cases, relatively small samples that are not representative at the national level (see Appendix in Rizvi & Hossain, 2017). The few cross-country studies on this topic also do not find a direct positive association between religiosity and happiness.…”
Section: Concluding Remark Smentioning
confidence: 94%